Combination of Entecavir/Peginterferon Alfa‐2a in Children With Hepatitis B e Antigen–Positive Immune Tolerant Chronic Hepatitis B Virus Infection. Issue 6 (20th February 2019) - Rosenthal, Philip; Ling, Simon C.; Belle, Steven H.; Murray, Karen F.; Rodriguez‐Baez, Norberto; Schwarzenberg, Sarah J.; Teckman, Jeffrey; Lin, Hsing‐Hua S.; Schwarz, Kathleen B.; ,
Abstract : The optimal management strategy for children with immune‐tolerant chronic hepatitis B virus (HBV) infection remains unknown. The purpose of this clinical trial was to determine the safety and efficacy of therapy with entecavir and peginterferon in a group of children in the immune‐tolerant phase of HBV infection. Children with immune‐tolerant features of chronic hepatitis B (CHB) received entecavir once‐daily in a dose of 0.015 mg/kg (0.5 mg maximum) for 48 weeks; peginterferon alfa‐2a (180 µg/1.73m 2 subcutaneously) once‐weekly was added at the end of week 8 and continued until week 48. The primary endpoint was lack of detectable hepatitis B e antigen (HBeAg) with HBV DNA levels ≤1, 000 IU/mL 48 weeks after stopping therapy. Sixty children (75% female), median age 10.9 (range, 3.4‐17.9) years, were enrolled. All were positive for hepatitis B surface antigen (HBsAg) and HBeAg and had high levels of HBV DNA with normal or minimally elevated levels of alanine aminotransferase (ALT). Fifty‐five children completed the entire 48‐week course of therapy. At 48 weeks after treatment ended (week 96), 2 children (3%) achieved the primary endpoint and were also HBsAg negative and anti–hepatitis B surface antigen antibody (anti‐HBs) positive. One child was HBeAg positive but HBsAg negative at week 60; another was HBeAg negative but HBsAg positive at week 72, which were their last clinic visits. In the remaining children, serum ALT and HBV DNA levels at week 96 were similar to baseline. Thirty‐seven children experienced adverse events (AEs), and 1 had a serious AE (SAE). Conclusion: The combination of entecavir and peginterferon for up to 48 weeks rarely led to loss of HBeAg with sustained suppression of HBV DNA levels in children in the immune‐tolerant phase of HBV infection, and treatment was associated with frequent AEs.